Stakeholders and resources in public hospitals. Towards an integrated view - Austen, Agata; Frąckiewicz, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
Background Public organizations need to satisfy their stakeholders to obtain political legitimization and the resources that follow it. According to the resource dependence theory (RDT), organizations should pay more attention to the stakeholders who control resources critical to the organization than to stakeholders who do not control vital resources. On the other hand, consistent with the resource based view (RBV), if they are to operate, act on opportunities and minimize threats, which is necessary to satisfy key stakeholders, they need resources and capabilities. Thus stakeholders might be seen as a link between external and internal resources. Purposes Our research attempted to comprehend the logic of strategic choices referring to stakeholders and resources. The underlying question was about the ability of recognizing the resources necessary for operating and satisfying key stakeholders. We attempt to thoroughly understand the decisions taken by public hospitals in relation to their stakeholders and the resources needed for their operation. Providing quantitative findings, we aim at answering the question how the resource based view (RBV), resource dependence theory (RDT) and stakeholder management can be used to explain the decisions made in public organizations in terms of stakeholder management
Argumenta Oeconomica, 2018, Nr 1 (40), s. 253-274
Keywords: stakeholders; RBV; RDT; organizational effectiveness; public hospitals